2022
DOI: 10.3389/fmicb.2022.1050271
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular vesicles produced by the human gut commensal bacterium Bacteroides thetaiotaomicron elicit anti-inflammatory responses from innate immune cells

Abstract: Bacterial extracellular vesicles (BEVs) produced by gut commensal bacteria have been proposed to play an important role in maintaining host homeostasis via interactions with the immune system. Details of the mediators and pathways of BEV-immune cell interactions are however incomplete. In this study, we provide evidence for the anti-inflammatory and immunomodulatory properties of extracellular vesicles produced by the prominent human gut commensal bacterium Bacteroides thetaiotaomicron (Bt BEVs) and identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Since BEVs from LAB lack protein markers like the flagellin of EcN, we employed an anti‐inflammatory bioactivity assay to track AEC purification of L. casei BEVs. We selected macrophages to study since this cell type is implicated in pathology of chronic inflammatory diseases such as inflammatory bowel disease, and signal with probiotic BEVs derived from bacteria present in the gut microbiome (Dharmasiri et al, 2021; Fonseca et al, 2022). To enable iterative development of our purification method in a high throughput fashion, we utilized the mouse macrophage cell line RAW264.7.…”
Section: Resultsmentioning
confidence: 99%
“…Since BEVs from LAB lack protein markers like the flagellin of EcN, we employed an anti‐inflammatory bioactivity assay to track AEC purification of L. casei BEVs. We selected macrophages to study since this cell type is implicated in pathology of chronic inflammatory diseases such as inflammatory bowel disease, and signal with probiotic BEVs derived from bacteria present in the gut microbiome (Dharmasiri et al, 2021; Fonseca et al, 2022). To enable iterative development of our purification method in a high throughput fashion, we utilized the mouse macrophage cell line RAW264.7.…”
Section: Resultsmentioning
confidence: 99%
“…involved in the proinflammatory response to infection [83]. More research has shown that trained immunity can be induced by non-specific stimuli, such as exposure to microbial components like OMVs [22,23]. OMVs also play a significant role in suppressing the host immune response in CF, where chronic bacterial infections are established in a thick mucus layer in the lungs overlying epithelial cells, limiting direct contact of the invading pathogens with host lung epithelia [85].…”
Section: Omvs Alter the Host Immune Response To Subsequent Bacterial ...mentioning
confidence: 99%
“…A few recent studies have linked bacterial OMVs to changes in methylation of immune cell genes, altering their response to infection. For example, B. thetaiotaomicron OMVs ameliorated chronic intestinal inflammation in a mouse model by increasing methylation of the 4th lysine residue of the histone H3 protein in murine bonemarrow-derived macrophages [23]. On the other hand, treatment with OMVs secreted by P. aeruginosa caused a decrease in the methylation of CpG sites in human lung macrophages, which had a strong negative correlation with pro-inflammatory immune cytokine gene OMVs also play a significant role in suppressing the host immune response in CF, where chronic bacterial infections are established in a thick mucus layer in the lungs overlying epithelial cells, limiting direct contact of the invading pathogens with host lung epithelia [85].…”
Section: Omvs Alter the Host Immune Response To Subsequent Bacterial ...mentioning
confidence: 99%
“…Because they convey various molecules and are taken up by host cells in the immediate vicinity, parasite EVs appear as logical players in trained immunity. However, evidence that EVs can indeed induce trained immunity is limited, although it has recently been shown that EVs from intestinal bacteria can cause trained immunity in bone marrow-derived macrophages in vitro , and also decrease the IL-10 and TNF responses to LPS Stimulation ( 220 ). EVs from monocytes containing the HIV component Nef (negative factor) were also shown to cause long-term hyperactivity in monocytes in an epigenetic and metabolic rewiring-dependent mechanism ( 221 ).…”
Section: Alternatives To Humoral Immunity As a Vaccine Strategymentioning
confidence: 99%